Crown Preservation of the Mandibular First Molar Tooth Impacts the Strength and Stiffness of Three Non-Invasive Jaw Fracture Repair Constructs in Dogs - Lothamer, Charles; Snyder, Christopher John; Duenwald-Kuehl, Sarah; Kloke, John; McCabe, Ronald P.; Vanderby, Ray (Frontiers in Veterinary Science, 2015)
Repairing mandibular body fractures present unique challenges not encountered when repairing long bones. Large tooth roots and the presence of the inferior alveolar neurovascular bundle limit safe placement for many types of orthopedic implants. Use of noninvasive fracture repair methods have increasingly become popular and have proven safe and effective at achieving bone healing. Noninvasive fixation constructs have not been tested in dogs using cantilevered bending. Furthermore noninvasive fracture repair constructs have not been tested at the location of a common fracture location- the mandibular first molar tooth (M1). The objectives of this study were to test the strength and stiffness of three noninvasive mandibular fracture repair constructs and to characterize the impact that tooth crown preservation has on fixation strength for fractures occurring at the M1 location. Specimens were assigned to three treatment groups: (1) composite only, (2) interdental wiring and composite and (3) transmucosal fixation screw and composite. For each pair of mandibles, one mandible received crown amputation at the alveolar margin to simulate the effect of crown loss on fixation strength and stiffness. Regardless of the status of crown presence, interdental wiring and composite demonstrated the greatest bending stiffness and load to failure. With the crown removed, interdental wiring and composite was significantly stronger compared to other treatments. All fixation constructs were stiffer when the tooth crown was preserved. In fractures at this location, retaining the tooth crown of M1 significantly increases stiffness of interdental wiring with composite and transmucosal screw with composite constructs. If the crown of M1 was removed, interdental wiring and composite was significantly stronger than the other two forms of fixation.